Equation predicting tibial-tuberosity to trochlear-groove distance following supratubercle osteotomy: Radiographic proof of concept. (February 2023) - Bozzo, Isabella; Laverdière, Carl; Corban, Jason; Ge, Susan; Pauyo, Thierry; Bernstein, Mitchell
Abstract: Background: Supratubercle tibial rotational osteotomies are useful in patellar stabilizing procedures with high tibial-tuberosity to trochlear-groove distance caused by excessive external tibial torsion. An investigation determined one degree of internal tibial rotation results in 0.68 mm reduction of tibial-tuberosity to trochlear-groove distance, but did not account for anatomical variability. Methods: This is a radiographic proof of concept for equation validation. We compared two different derived equations, a complex four-variable and simplified two-variable equation, to the literature relationship and true measured value from CT imaging. Bilateral pre-operative CTs of 37 patients, evaluated for malalignment, were reviewed retrospectively. We virtually simulated derotations of five, ten and fifteen degrees, and compared the reduction in tibial-tuberosity to trochlear-groove distance measured radiologically from CTs to the one predicted by our equation. Findings: The difference between the true change in tibial-tuberosity to trochlear-groove distance and that obtained using our four-variable was statistically insignificant for all derotation angles ( p > 0.05), and the two-variable equation it was statistically insignificant for five and fifteen degrees of derotation (p > 0.05). Conversely, the true values were statistically different from those found using the published relationship ( p < 0.05 for all). Interpretation: This new equation accounts for individual patient anatomy, for a more accurate relationship between internal rotation of the distal segment of the tibia and the subsequent decrease in the tibial-tuberosity to trochlear-groove distance. The change was overestimated using the linear relationship, which may result in under correction. Future studies will assess true post-operative distance change following osteotomy. Highlights: Malalignment syndrome can be treated with supratubercle derotational osteotomy. Change in tibial tuberosity to trochlear groove length aids in surgical planning. Derived an equation for the length change in supratubercle derotational osteotomy. Validated the novel equation with pre-operative CT imaging. First equation which accounts for unique patient anatomy to predict length change.